Advantages of Tooth Movement Using Orthodontic Microimplants in the Treatment of Dentofacial Anomalies - Zakalata, T.; Burlaka, V. (Actual Dentistry, 2026)
Analysis of the advantages arising from the use of microimplants in orthodontic treatment. A high success rate is observed across cases involving different implant sizes. The versatility of microimplants ensures their applicability in orthodontic management of various conditions and defects.